Interference lithographic nanopatterning of plant and bacterial light-harvesting complexes on gold substrates - Patole, Samson (Interface Focus, 2015)
We describe a facile approach for nanopatterning of photosynthetic light-harvesting complexes over macroscopic areas, and use optical spectroscopy to demonstrate retention of native properties by both site-specifically and non-specifically attached photosynthetic membrane proteins. A Lloyd's mirror dual-beam interferometer was used to expose self-assembled monolayers of amine-terminated alkylthiolates on gold to laser irradiation. Following exposure, photo-oxidized adsorbates were replaced by oligo(ethylene glycol) terminated thiols, and the remaining intact amine-functionalized regions were used for attachment of the major light-harvesting chlorophyll–protein complex from plants, LHCII. These amine patterns could be derivatized with nitrilotriacetic acid (NTA), so that polyhistidine-tagged bacteriochlorophyll–protein complexes from phototrophic bacteria could be attached with a defined surface orientation. By varying parameters such as the angle between the interfering beams and the laser irradiation dose, it was possible to vary the period and widths of NTA and amine-functionalized lines on the surfaces; periods varied from 1200 to 240 nm and linewidths as small as 60 nm (λ/4) were achieved. This level of control over the surface chemistry was reflected in the surface topology of the protein nanostructures imaged by atomic force microscopy; fluorescence imaging and spectral measurements demonstrated that the surface-attached proteins had retained their native functionality.